STRATEGIES TO ENHANCE BUSINESS GROWTH THROUGH ENTREPRENEURIAL LEARNING - Prety Diawati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
This study examines the effects of work experience, self-efficacy, and access to finance on business growth, with entrepreneurial learning as a mediating variable. It employs a quantitative approach with SEM-PLS methodology. It investigated 100 MSMEs in Subang Regency, Indonesia and conducted surveys via online questionnaires. As a result, this study indicates that work experience, self-efficacy, and access to finance significantly impact MSME business growth through entrepreneurial learning. Entrepreneurs with more diverse and relevant work experience are better in absorbing and applying new knowledge, and driving business growth. Their high self-efficacy boosts participation in training and the application of new skills, leading to income growth, market expansion, and employee increases. This study also presents the importance of developing entrepreneurial training programs that cater to MSMEs’ specific needs, considering work experience and self-efficacy levels. Furthermore, this study highlights the need for the government and financial institutions to improve MSMEs' access to finance, such as by expanding the People's Business Credit (KUR) and offering other supportive measures to help entrepreneurs invest in learning and business development.